PENGARUH UKURAN PERUSAHAAN, CAPITAL INTENSITY DAN KEPEMILIKAN MANAJERIAL TERHADAP AGRESIVITAS PAJAK (Studi Empiris Perusahaan Manufaktur Sektor Food Dan Beverage yang Terdaftar di BEI Tahun 2017-2021) - Julinda Ramdani; Yulianto Yulianto (JURNAL PUNDI, 2023)
This study aims to determine the effect of Company Size, Capital Intensity and Managerial Ownership on Tax Aggressiveness in manufacturing companies in the Food and Beverage sector listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The type of research used is quantitative. The sample selection was carried out based on the purposive sampling method, so that the samples obtained were 10 (ten) companies. The data analysis technique used is panel data regression. With data management using the Eviews 9 program. The results showed that simultaneously the variables Firm Size, Capital Intensity and Managerial Ownership have an effect on Tax Aggressiveness. Partially, Company Size has an effect on Tax Aggressiveness, Capital Intensity has no effect on Tax Aggressiveness and Managerial Ownership has an effect on Tax Aggressiveness. Keywords: Company Size; capital intensity; managerial ownership; Tax Aggressiveness